Pengendalian Penyelesaian Proyek Berbasis Kinerja Menggunakan Hybrid Earned Value - Crash Program - Soetjipto, Jojok Widodo; Adinanda, Della Ayu; Arifin, Syamsul (Jurnal Aplikasi Teknik Sipil, 2025)
Project performance is an essential reference in supporting the success of construction implementation so that costs and completion time are according to plan. Previous research states that projects that experience delays will impact cost overruns which can be detrimental to contractors and project owners. This study takes the case of a performance evaluation on a building construction project that experienced a delay of 15.496% (25th week). The performance measurement results using the earned value, the project has an SPI value = 0.493, meaning that the project experienced significant delays. If the project is not controlled, it will take 72 weeks to complete from the 48-week plan at the cost of Rp. 64.57 billion from Rp. 57.23 billion. Control of this project needs acceleration which was carried out using the Crash Program method in 2 ways: (i) increasing the number of workers and (ii) maintaining the number of existing workers but increasing overtime hours. A practical solution alternative is to increase the number of workers, which results in a project completion time of 43 weeks with a final project cost of IDR 58.89 billion